Great escape at Dunkirk - Fisher, John Hayes; Meyers, Eric, 1959-; Public Broadcasting Service (U.S.); Blink Entertainment Ltd. ([Arlington, VA] : PBS, 2018)
Join archaeologists and divers recovering remains of ships and planes lost during World War II's epic Dunkirk operation. Discover new evidence of the ingenious technology that helped save Allied forces from defeat by the encircling Germans.
Title from title screens.
Originally produced in 2017.
Wide screen (16x9).
Edited by Danny Boocock, Bill Coates; camera, Paul Lang, Tom Hayward, Kevin Young.
Narrator: Eric Meyers.
Originally broadcast by PBS Feb. 18, 2018.
Keywords: 1939-1945; World War II -- Campaigns -- France -- Dunkerque; World War, 1939-1945 -- Search and rescue operations -- France -- Dunkerque; Search and rescue operations; Military campaigns; Video recordings for the hearing impaired